Characterization of a New Transposon, Tn6696, on a blaNDM–1-Carrying Plasmid From Multidrug-Resistant Enterobacter cloacae ssp. dissolvens in China - Chen, Qichao; Lin, Yanfeng; Li, Zhonghong; Lu, Lanfen; Li, Peihan; Wang, Kaiying; Yang, Lang; Ma, Hui; Li, Peng; Song, Hongbin (Frontiers in Microbiology, 2020)
Background Enterobacter cloacae is an opportunistic pathogen which is responsible for serious nosocomial infections. A gene which plays an important role in resistance to carbapenems is the New Delhi metallo-β-lactamase 1 (NDM-1). Currently, the spread of NDM-1-producing E. cloacae strains is a serious public threat. Methods A multidrug-resistant E. cloacae ssp. dissolvens strain CBG15936 was recovered in 2017 in Guangzhou, China. PCR, S1-pulsed-field gel electrophoresis, and Southern blotting were performed to locate the blaNDM–1 gene. Susceptibility testing and conjugation experiments were also performed. Illumina HiSeq and Nanopore sequencers were used to perform whole-genome sequencing. Results Strain CBG15936 belongs to ST932 and is resistant to carbapenems. The blaNDM–1 gene was found on a ∼62-kb plasmid, which has a conjugation frequency of 1.68 × 10–3 events per donor cell. Genome sequencing and analysis revealed that the NDM-1-carrying IncN1 plasmid contained a new transposon Tn6696, which consists of an intact qnrS1-carrying Tn6292 element, an inverted 8.3-kb Tn3000 remnant, ISkpn19, ΔtnpA, and IS26. Conclusion A new transposon, Tn6696, has been detected on a blaNDM–1-carrying plasmid recovered from multidrug-resistant E. cloacae ssp. dissolvens CBG15936 from China. This finding provides a new perspective regarding the potential for blaNDM–1 to undergo horizontal transfer among drug-resistant bacteria.